Tratamento clínico ou cirúrgico em cães com extrusão de disco intervertebral (Hansen tipo I) toracolombar - Chaves, Rafael Oliveira (2017)
The extrusion of the intervertebral disc is the most common cause of neurological disorders in dogs. Extrusion (Hansen type I) or protrusion (Hansen type II) of the disc may occur and consequent compression of the spinal cord and / or nerve roots. The objective of this thesis was, in a first step, to carry out a retrospective study for the epidemiological survey of the disease and to evaluate dogs in different degrees of neurological dysfunction after surgical decompression of the spinal cord. In article 1, of the 110 dogs with thoracolumbar DDIV submitted to surgical decompression, 74 (67.3%) improved clinical signs, 54 (49.1%) considered satisfactory and 20 (18.2%) were partially satisfactory. In article 2, of the 17 dogs with extrusion (Hansen type I) of thoracolumbar intervertebral disc without perception to deep pain (PDP) submitted to clinical treatment, nine (52.9%) presented satisfactory functional recovery, one (5.9%) satisfactory recovery without pain (Spinal walk) and seven (41.2%) were unsatisfactory. Of the 20 dogs submitted to surgical treatment, 10 (50%) presented satisfactory functional recovery, three (15%) satisfactory recovery without deep pain (spinal gait) and seven (35%) were unsatisfactory. There was no significant difference in functional recovery between dogs undergoing clinical or surgical treatment. In view of the results, the surgical treatment promotes a satisfactory functional recovery in the most of dogs with thoracolumbar disc extrusion, being the percentage of relapse in animals submitted to this type of therapy low. The functional clinical recovery in dogs with paraplegic thoracolumbar intervertebral disc extrusion and without perception to deep pain over 48 hours can occur independently of the treatment instituted. Other studies are needed with more cases to reinforce the evidence found.